Microstructure and wear performance of alumina/graphene coating on textured Al2O3/TiC substrate composites. Issue 2 (February 2021) - Liu, Changxia; Sun, Junlong; Venturi, Federico; Romero, Acacio Rincon; Hussain, Tanvir
Abstract: The incorporation of graphene-based nanodispersoids in ceramic coatings is known to enhance the wear behavior of these materials. In this study, for the first time, alumina/graphene nanoplatelets (GNPs) coatings were deposited through Suspension High Velocity Oxy-Fuel (SHVOF) thermal spray on Al2 O3 /TiC substrate composites, which were laser microtextured with grid and line surface patterns. Dense coatings with around 8−10 μm thickness were obtained by spraying alumina suspension containing 1 wt. % GNPs. The tribological performance of the alumina/GNPs coatings on the Al2 O3 /TiC substrate composites was evaluated using ball-on-disc sliding wear tests. The alumina/GNPs coated Al2 O3 /TiC substrate composites textured with grid pattern showed the best tribological performance reaching a steady coefficient of friction (CoF) at lower sliding distances and presenting the lowest wear rate of the Al2 O3 /TiC substrate composites and the counterbody.